Legal and Institutional Framework for Combating Cybercrimes in Nigeria - Daudu S. O.; Idehen S. O. (LexScriptio A Journal of the Department of Jurisprudence and Public Law, 2024)
This article examines the current legal and institutional regime for combating cybercrimes in Nigeria. It shall in adeptly examine the Cybercrime Act in combating cybercrimes in Nigeria and also examine the laws combating cybercrime in other jurisdictions such as the UK and USA. The discussion shall also cover the effectiveness of the legal framework aimed at combating cybercrimes in Nigeria, and the challenges affecting the fight against cybercrimes in Nigeria and some selected jurisdictions. As the use of digital technologies and internet connectivity has increased in Nigeria, the incidence of cybercrimes such as hacking, software piracy, and credit card fraud has also risen. In response, the Nigerian government enacted the Cybercrime Act in 2015 to prohibit, prevent, and punish cybercrimes through a comprehensive legal framework. The key law regulating cybercrime in Nigeria is the Cybercrime Act of 2015. This Act aims to create a robust legal regime to combat cybercrimes by defining offences and prescribing penalties. Other relevant laws include the Criminal Code Act, Money Laundering Act, and the Nigerian Communications Act. Countries such as the UK and USA have also enacted laws to tackle the borderless nature of cybercrimes. In 1996, the Council of Europe drafted an international treaty on computer crimes. The US enacted laws like the USA Patriot Act, 2003 to expand law enforcement powers online. However, effectively enforcing these laws in Nigeria is still challenging due to factors like transnational nature of crimes, lack of technical capacity, and inadequate public awareness. This negatively impacts the fight against cybercrimes in Nigeria.